Integrating Technology in Grade 10 Geography: Enhancing Basic Concepts with Geographic Information Systems - Susilawati, Siti Azizah; Hamisi, Salum Haji (Assyfa Learning Journal, 2025)
Integrating technology into geography education enhances students’ understanding of basic concepts in the digital era. This study employs a Research and Development (R&D) approach to create GIS-based learning media for 10th graders, focusing on maps, remote sensing, and the physical geosphere (lithosphere, atmosphere, hydrosphere) as living spaces. Sixty students participated, selected based on their initial geography knowledge and digital skills. The developed media were tailored to local needs and supported by a flexible curriculum. Results indicate a 25% improvement in students’ geography understanding, notably in spatial analysis and problem-solving skills. Challenges include limited technology infrastructure and the need for teacher training. Successful GIS integration requires educator support and guidance. Recommendations include developing teacher training programs on GIS use in geography and ensuring schools have adequate technology infrastructure. Collaboration among educators, policymakers, and technology developers is crucial for effective implementation. Further research should explore sustainable strategies and their educational impact.